Equilibrium shapes of director in nematic with cylindrical particles - Ledney, M.F. (Functional Materials, 2005)
Equilibrium shapes of the director arising around a cylindrical particle in nematic liquid crystal are studied in their dependence upon the value and type of anchoring between the director and the lateral surface of the particle. Perpendicular and parallel orientations of the particle axis with respect to the non-perturbed nematic director are considered. In the case of strong anchoring between the director and the lateral surface of the particle the equilibrium distance between the axis of the particle and a disclination line is obtained as a function of value anchoring energy. In the case of weak anchoring for nematic in external electric field the analytical expression for the distribution of the director field around the cylindrical particle is obtained.